Comparison of Diffusion Kurtosis Imaging and Amide Proton Transfer Imaging in the Diagnosis and Risk Assessment of Prostate Cancer - Yin, Huijia; Wang, Dongdong; Yan, Ruifang; Jin, Xingxing; Hu, Ying; Zhai, Zhansheng; Duan, Jinhui; Zhang, Jian; Wang, Kaiyu; Han, Dongming (Frontiers in Oncology, 2021)
Objectives: This study aims to evaluate and compare the diagnostic value of DKI and APT in prostate cancer (PCa), and their correlation with Gleason Score (GS). Materials and methods: DKI and APT imaging of 49 patients with PCa and 51 patients with benign prostatic hyperplasia (BPH) were collected and analyzed, respectively. According to the GS, the patients with PCa were divided into high-risk, intermediate-risk and low-risk groups. The mean kurtosis (MK), mean diffusion (MD) and magnetization transfer ratio asymmetry (MTRasym, 3.5ppm)values among PCa, BPH, and different GS groups of PCa were compared and analyzed respectively. The diagnostic accuracy of each parameter was evaluated by using the receiver operating characteristic (ROC) curve. The correlation between each parameter and GS was analyzed by using Spearman’s rank correlation. Results: The MK and MTRasym(3.5ppm) values were significantly higher in PCa group than in BPH group, while the MD value was significantly lower than in BPH group. The differences of MK/MD/MTRasym (3.5ppm) between each two of the low-risk, intermediate-risk, and high-risk groups were all statistically significant(p < 0.05). The MK value showed the highest diagnostic accuracy in differentiating PCa and BPH, BPH and low-risk, low-risk and intermediate-risk, intermediate-risk and high-risk (AUC=0.965, 0.882, 0.839, 0.836). The MK/MD/MTRasym(3.5ppm) values showed extremely and moderate strong correlation with GS ( r=0.844, -0.811, 0.640, p < 0.05), respectively. Conclusion: DKI and APT imaging are valuable in the diagnosis of PCa and demonstrate strong correlation with GS, which has great significance in the risk assessment of PCa.